2023
DOI: 10.1017/s1041610222000382
|View full text |Cite
|
Sign up to set email alerts
|

The effect of creative expression program in neurocognitive networks performance measured by task and resting-state functional MRI

Abstract: Background: The current study examined the effects of a 16-week creative expression program on brain activity during a story creating task and resting-state functional network connectivity in mild cognitive impairment (MCI) adults. Method: Thirty-six MCI adults were allocated to either the creative expression program (CrExp, n = 18) or control group (CG,n = 18). Before and after intervention, all participants were scanned with functional magnetic resonance imaging (fMRI) during story cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Creative expression intervention usually involves art activities such as drawing, storytelling, and group discussion, as Zhao et al (2022) designed. The cognitive stimulating training program is another nonpharmacology intervention based on the theory of "use it or lose it."…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Creative expression intervention usually involves art activities such as drawing, storytelling, and group discussion, as Zhao et al (2022) designed. The cognitive stimulating training program is another nonpharmacology intervention based on the theory of "use it or lose it."…”
mentioning
confidence: 99%
“…In the current issue of International Psychogeriatrics , Zhao and colleagues reported that a 25-session creative expression intervention may shape the brain function of individuals with MCI (Zhao et al ., 2022). Using task-related functional magnetic resonance imaging (fMRI), researchers observed an increased brain activation in the right anterior cingulate gyrus, the right middle frontal gyrus, the right lentiform nucleus, the left hippocampus, the left middle occipital gyrus, and the left cerebellum posterior lobe in the intervention group.…”
mentioning
confidence: 99%
See 3 more Smart Citations